Exploring the influence of problematic smartphone use on physical activity: chain mediation of Self-Control and Exercise Procrastination and moderation by Independent and Interdependent Self-Construal - Yibo Shen; Taeyang Yang; Gyuil Lee (Frontiers in Psychology, 2026)
Objective With smartphones deeply integrated into college students’ daily lives, Problematic Smartphone Use (PSU) may become a significant risk factor affecting Physical Activity (PA). Based on self-regulation theory and self-construal theory, this study aims to examine the relationship between PSU and college students’ PA, and further investigate the chain mediation effects of Self-Control (SC) and Exercise Procrastination (EP), as well as the moderating roles of Independent Self-Construal (IND) and Interdependent Self-Construal (INT). Methods A large-sample questionnaire survey was conducted, collecting 1,049 valid responses from college students across four provinces in China. Established scales were used for measurement. SPSS 31.0 and AMOS 31.0 were employed for descriptive statistics, correlation analysis, and confirmatory factor analysis. Two moderated chain mediation models were constructed, with the moderating variable being IND (Model 1) and INT (Model 2), respectively. Direct, indirect, and moderating effects were examined using a bootstrap procedure with 5,000 resamples. PROCESS Model 1 was used to generate slope plots for high and low levels of IND and INT. Results PSU negatively predicted college students’ PA. The single mediation effect of SC was not statistically significant, while the single mediation effect of EP was significant. A significant chain mediation pathway from SC to EP was identified. Self-Construal (Independent vs. Interdependent) significantly moderated the link between SC and EP in the chain mediation process. Conclusion PSU is closely associated with insufficient PA among college students. This association may be explained by a sequential psychological-behavioral mechanism in which lower SC is linked to increased EP. Self-Construal serves as a boundary condition in this process, indicating that the association between PSU and PA may vary depending on individuals’ self-understanding.